The impact of the 2022 Ukraine/Russian conflict on cancer clinical trials. Issue 12 (December 2022) - Talbot, Alice; Connor, Sophia G.; Austin, Kate; Hannon, Tara; Gabbay, Eli; Clay, Timothy D.
Since the invasion of Ukraine in February 2022, clinical trial conduct has become extremely challenging due to damage to the healthcare infrastructure and patient displacement. This current study aimed to estimate the number of cancer clinical trials at risk of impact from the conflict. A descriptive analysis and narrative review were completed using data from cancer clinical trials with sites in Russia or Ukraine using the 'clinical trials.gov' online database between February 2022 and May 2022. There were 508 clinical trials involving sites in Ukraine or Russia. Most were multinational studies (470 of 508; 93%). The majority of studies were phase 3 (344 of 508; 68%) and these also had the largest sample sizes (median 624, range 12–5637). The most common tumour types were lung (128 of 508; 25%), urogenital (94 of 508; 19%) and breast (78 of 508; 15%). A meaningful number of trials had curative intent (129 of 508; 25%). The most common intervention was immunotherapy-related (218 of 508; 43%), followed by other targeted therapy (185 of 508; 36%). Ukraine and Russia are both large centres for global clinical trial activity. The invasion of Ukraine may result in underpowering of international clinical trial results with loss of future recruitment sites for both countries.